Sistem Pendukung Keputusan Menentukan Status Karyawan Kontrak Sales Promotion Girl Menjadi Karyawan Tetap dengan Metode Simple Additive Weighting - Rudi Hartoyo (Yayasan Kita Menulis, 2021)
In selecting and determining contract employees such as Sales Promotion Girl (SPG) to become permanent employees in a company, it still seems inaccurate, because the assessment and calculation of the results of the test are done manually, so there is a possibility of errors in providing the final results of the selection. Therefore, a Decision Support System was designed that could determine SPG contract employees to become permanent employees who could assist the company in selecting the right employees. Decision Support Systems are part of a computer-based information system that is commonly used to support decision making in an organization or company. This decision support system is designed using the Simple Additive Weighting (SAW) method to calculate the results in determining SPG contract employees to become permanent employees. So, in the process of selecting SPG contract employees to become permanent employees using a decision support system using the SAW method can be done easily and precisely, because it is calculated by a computer system.